PREDICTION OF FACTORS INFLUENCING THE MANAGEMENT OF FREE ECONOMIC ZONES VIA CORRELATION-REGRESSION METHODS - Tokhtamurodov Davron Nizam ugli (Scholar Express Journals, 2025)
This article examines the activities of free economic zones in managing the effective use of investments, the foundations and importance of organizing the activities of free economic zones in the context of economic modernization. Factors affecting the organization of free economic zones in the regions by diversifying production, achieving competitiveness of national goods in domestic and foreign markets have been studied. Factors affecting the efficiency of management of free economic zones were scientifically forecasted through econometric models for the coming years. Practical recommendations of the author were put forward to improve the efficiency of management of free economic zones in the economy of Uzbekistan.
Keywords: Investment; free economic zone; investment attractiveness; localization